2004
DOI: 10.1017/s1479050504001164
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Biofilms

Abstract: The concept that bacteria live preferentially in matrix-enclosed communities attached to surfaces has emerged gradually from scientific observations over an extended period of time, but the pace at which this concept has advanced has accelerated sharply during the past two decades. Because Antonie van Leuwenhoek examined his own teeth scrapings with his primitive microscope, he probably saw more biofilm fragments than planktonic cells, and dental microbiologists and waste-water engineers have had a lengthy ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…The microorganisms observed are almost in every physiological state known, from aerobic to anaerobic and from exponential to stationary phases of growth 11 and they have a net negative surface charge usually behaving as hydrophobic particles 8 . Scaling and organic foulants usually originate from water and sometimes from other raw materials (e.g.…”
Section: Composition Of Soil Filmsmentioning
confidence: 99%
“…The microorganisms observed are almost in every physiological state known, from aerobic to anaerobic and from exponential to stationary phases of growth 11 and they have a net negative surface charge usually behaving as hydrophobic particles 8 . Scaling and organic foulants usually originate from water and sometimes from other raw materials (e.g.…”
Section: Composition Of Soil Filmsmentioning
confidence: 99%
“…Therefore, significant limitations exist when attempting to extrapolate planktonic culture susceptibility data to environmental or clinical scenarios where the majority of microbial growth is as biofilms. This is illustrated by the NIH estimation that up to 80% of all chronic human infections are biofilm-mediated and that 99.9% of bacteria in aquatic ecosystems live as biofilm communities (Lewis, 2001;Costerton & Wilson, 2004). Indeed, it has been demonstrated that there is often no correlation between planktonic susceptibility to antimicrobials (MIC values) and biofilm susceptibility of the same species and strain to those same antimicrobial agents (Smith et al, 2003).…”
Section: Antibiofilm Activity Of 1-alkyl-3-methylimidazolium Chloridementioning
confidence: 99%
“…Biofilme é um consórcio microbiano envolvido em uma matriz de polissacarídeos extracelulares resultante da aderência, multiplicação e desenvolvimento de microrganismos sobre superfícies sólidas. É geralmente formado em resposta às condições ambientais desfavoráveis, sendo o resultado de uma estratégia universal usada pelos microrganismos para otimizar a sobrevivência e perpetuação da espécie (15) .…”
Section: Resultsunclassified